Persistence of SARS-CoV-2 neutralizing antibodies longer than 13 months in naturally infected, captive white-tailed deer (Odocoileus virginianus), Texas. Issue 1 (31st December 2022) - Hamer, Sarah A.; Nunez, Chase; Roundy, Christopher M.; Tang, Wendy; Thomas, Logan; Richison, Jack; Benn, Jamie S.; Auckland, Lisa D.; Hensley, Terry; Cook, Walter E.; Pauvolid-Corrêa, Alex; Hamer, Gabriel L.
ABSTRACT: After identifying a captive herd of white-tailed deer in central Texas with >94% seroprevalence with SARS-CoV-2 neutralizing antibodies in September 2021, we worked retrospectively through archived serum samples of 21 deer and detected seroconversion of all animals between December 2020 and January 2021. We then collected prospective samples to conclude that the duration of persistence of neutralizing antibodies is at least 13 months for 19 (90.5%) of the animals, with two animals converting to seronegative after six and eight months. Antibody titres generally waned over this time frame, but three deer had a temporary 4- to 8-fold increases in plaque reduction neutralization test titres over a month after seroconversion; anamnestic response cannot be ruled out.